Matrix Architecture and Mechanics Regulate Myofibril Organization, Costamere Assembly, and Contractility in Engineered Myocardial Microtissues - Samuel J. DePalma; Javiera Jilberto; Austin E. Stis; Darcy D. Huang; Jason Lo; Christopher D. Davidson; Aamilah Chowdhury; Robert N. Kent III; Maggie E. Jewett; Hiba Kobeissi; Christopher S. Chen; Emma Lejeune; et al. (Advanced Science, 2024)
Abstract The mechanical function of the myocardium is defined by cardiomyocyte contractility and the biomechanics of the extracellular matrix (ECM). Understanding this relationship remains an important unmet challenge due to limitations in existing approaches for engineering myocardial tissue. Here, they established arrays of cardiac microtissues with tunable mechanics and architecture by integrating ECM‐mimetic synthetic, fiber matrices, and induced pluripotent stem cell‐derived cardiomyocytes (iPSC‐CMs), enabling real‐time contractility readouts, in‐depth structural assessment, and tissue‐specific computational modeling. They found that the stiffness and alignment of matrix fibers distinctly affect the structural development and contractile function of pure iPSC‐CM tissues. Further examination into the impact of fibrous matrix stiffness enabled by computational models and quantitative immunofluorescence implicates cell‐ECM interactions in myofibril assembly, myofibril maturation, and notably costamere assembly, which correlates with improved contractile function of tissues. These results highlight how iPSC‐CM tissue models with controllable architecture and mechanics can elucidate mechanisms of tissue maturation and disease.